2022
DOI: 10.5267/j.jpm.2021.9.002
|View full text |Cite
|
Sign up to set email alerts
|

Project scheduling and buffer management: A comprehensive review and future directions

Abstract: In the project management, buffers are considered to handle uncertainties that lead to changes in project scheduling which in turn causes project delivery delay. The purpose of this survey is to discuss the state of the art on models and methods for project buffer management and time optimization of construction projects and manufacturing industries. There are not literally any surveys which review the literature of project buffer management and time optimization. This research adds to the previous literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Zohrehvandi and Soltani discussed the state-of-the-art models and methods for buffer management and time optimization of projects and manufacturing industries. The results of this research showed that it is possible to implement buffer management in industries, factories, and projects and obtain satisfactory results [29]. Bie et al analyzed the effects of the dependence between activities on project duration performances and introduced a method for determining buffer sizes with a dependence assumption between activities [30].…”
Section: Literature Reviewmentioning
confidence: 86%
“…Zohrehvandi and Soltani discussed the state-of-the-art models and methods for buffer management and time optimization of projects and manufacturing industries. The results of this research showed that it is possible to implement buffer management in industries, factories, and projects and obtain satisfactory results [29]. Bie et al analyzed the effects of the dependence between activities on project duration performances and introduced a method for determining buffer sizes with a dependence assumption between activities [30].…”
Section: Literature Reviewmentioning
confidence: 86%
“…It is interesting to set up the buffer with the help of entropy theory. In addition, we can also draw on other concepts that can describe uncertainty, such as probabilistic rough sets, cloud models, fuzzy sets, etc., [52]. Undoubtedly, the study of buffers from a systems perspective needs more attention and this will be one of the key directions for future research on buffer settings.…”
Section: Discussionmentioning
confidence: 99%
“…Determining the size of the buffer in CCPM has been a constant concern among researchers, with numerous studies focusing on this dilemma [26][27][28]. There is not a single answer to this question, as it depends on the type of the project, ongoing monitoring, and control.…”
Section: Literature Reviewmentioning
confidence: 99%